The King and the Crown of Thorns Kingship and the Cult of Relics in Capetian France - Pysiak, Jerzy (Peter Lang International Academic Publishing Group, 2021)
In 1239, king Louis IX of France performed the translation of the Crown of Thorns from Constantinople to Paris. The translation celebrations became a splendid religious festivity showing sacral foundations of Saint Louis's authority and the Capetian kingship. However, the translation of the Crown of Thorns to France had already a history under Louis's reign: French hagiographers and chroniclers affirmed that the first relics of the Crown of Thorns from Constantinople were transferred to Aachen by Charlemagne, then to Saint-Denis Abbey by Charles the Bald. The book discusses Saint Louis's translation of the Crown of Thorns as seen on the background of both Carolingian historical memory in Capetian era and Carolingian and Capetian tradition of the royal cult of relics.